THE SUSTAINABLE TOURIST AS AN AGENT OF CHANGE: RESPONSIBILITIES, ETHICAL CONDUCT, AND IMPACT IN UZBEKISTAN’S TOURISM DEVELOPMENT - Khusniddin Egamnazarov (Modern American Journals, 2025)
This paper explores the role of the sustainable tourist as an agent of change in Uzbekistan’s tourism sector, focusing on their responsibilities, ethical conduct, and impact on sustainable development. Drawing on an integrative conceptual model, the study examines how ethical cognition, behavioral intentions, and contextual factors influence tourists’ actual sustainable behaviors. Data collected through surveys were analyzed using descriptive and inferential statistics to identify key predictors of sustainable tourist behavior. Findings reveal that while ethical awareness significantly shapes behavioral intentions, external enablers and barriers critically affect the translation of intention into action. The study highlights the importance of multi-stakeholder collaboration, infrastructure development, and educational initiatives to empower tourists in promoting sustainability. Recommendations are offered to policymakers and industry practitioners to enhance sustainable tourism practices in Uzbekistan, fostering ecological preservation, cultural respect, and community well-being.
Keywords: Sustainable tourism, Ethical tourism, Tourist behavior, Uzbekistan, Sustainable development, Behavioral intention, Tourism impact